Video Edukasi Kesehatan Untuk Meningkatkan Pengetahuan First Aid Kejadian Luka Bakar - Lailaturohmah Kurniawati; Cindi Realita Fatmawati Putri; Dwi Murtini (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Burns are the fifth leading cause of unintentional injury-related death in children. The importance of knowledge that must be possessed by children in providing first aid for burn cases in children, can reduce disability and morbidity rates. The purpose of the service activity is to provide Video health education to school-age children at MI Muhammadiyah Waru Elementary School about the first handling of burns. The method of service is by using game-based learning in the form of oral presentation of material and animated videos about the first handling of burns. The data analysis method used in this service activity is PrePost-Experimental design, Participants in this activity are elementary school-age children MI held on November 11, 2023. The educational materials provided are the causes of burns, types of burns, management and prevention of burns. Then, the service team conducted education related to handling burns to respondents. The conclusion is that after this education is carried out, respondents can understand and know the reasons for handling burns should not be arbitrary because it can cause more severe infections.